Chlorogenic Acid Suppresses miR‐155 and Ameliorates Ulcerative Colitis through the NF‐κB/NLRP3 Inflammasome Pathway. Issue 23 (9th November 2020) - Zeng, Junhao; Zhang, Dengqing; Wan, Xiaoyu; Bai, Yuanling; Yuan, Chengfu; Wang, Ting; Yuan, Ding; Zhang, Changcheng; Liu, Chaoqi
Abstract : Scope: The over‐activation of the nucleotide‐binding domain like receptor protein 3 (NLRP3) inflammasome plays an important role in the pathogenesis of ulcerative colitis (UC). Chlorogenic acid (CGA) exposure is identified as an effective strategy for repressing inflammatory responses. Methods and results: In this study, the NLRP3 inflammasome model with LPS/ATP‐induced RAW264.7 cells in vitro and dextran‐sulfate‐sodium (DSS)‐induced colitis in mice are used to evaluate the effect of CGA on NLRP3 inflammasome‐related signaling. The results suggest that CGA suppressed the expression of NLRP3 inflammasome‐related genes (apoptosis‐associated speck‐like protein containing CARD (ASC), cysteine‐requiring aspartate protease (Caspase)‐1 p45, Caspase‐1 p20, pro‐/cleaved‐interleukin (IL)‐1β, pro‐/cleaved‐IL‐18), p‐nuclear factor kappa B (NF‐κB) protein, and miR‐155 in mice with colitis. Gain‐ and loss‐of‐function studies of miR‐155 are performed to elucidate its role in inflammation. Moreover, activation of the NF‐κB/NLRP3 inflammasome pathway and miR‐155 expression is investigated. CGA exposure in lipopolysaccharide (LPS)/adenosine triphosphate (ATP)‐stimulated RAW264.7 cells leads to a decrease in p‐NK‐κB and NLRP3 inflammasome‐related proteins, which is dependent on the downregulation of miR‐155 expression. Conclusions: These findings indicate that CGA prevented colitis by downregulating miR‐155 expression and inactivating the NF‐κB/NLRP3 inflammasome pathway in macrophages. The current study has promising therapeutic implications in the treatment of UC. Abstract : Utilizing LPS and ATP exposure, NF‐κB and NLRP3 inflammasome activation is induced in RAW264.7 murine macrophages, in which miR‐155 is overexpressed. Chlorogenic acid can inhibit miR‐155 expression, which causes decreases of NF‐κB and inflammasome constituent protein, namely NLRP3, ASC, and Caspase‐1. Consequently, both inactive precursors and mature forms of IL‐1β and IL‐18 are attenuated, and inflammatory responses are inhibited.